Friday

April 18, 2014

April 18, 2014

Posted by **Sam** on Wednesday, May 2, 2012 at 9:57pm.

- Math -
**Bosnian**, Wednesday, May 2, 2012 at 10:21pm18 x ^ 5 + 3 x ^ 3 + 6 x = 3 x ( 6 x ^ 4 + x ^ 2 + 2 )

( 18 x ^ 5 + 3 x ^ 3 + 6 x ) / 3 x = 3 x ( 6 x ^ 4 + x ^ 2 + 2 ) / 3 x =

( 3 x / 3 x ) ( 6 x ^ 4 + x ^ 2 + 2 ) =

1 * ( 6 x ^ 4 + x ^ 2 + 2 ) =

6 x ^ 4 + x ^ 2 + 2

**Related Questions**

Algebra - checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4...

BobPursley..here it is: - Problem 1: (x-2)/(3x+4) - 6x/(x+1) What I did: Common ...

math - simplify (x^2-3x+6)-(36x^2-18x+6/6) (x^2-3x+6)-(6(6x^2-3x+1/6) cancel the...

Math - Can someone please check my answers below for accurateness? The ...

Pre-algebra - I have some practice problems, and I need to have them worked out...

Pre-algebra - I have some practice problems, and I need to have them worked out...

math - 3x-4=-2(3x+5) 3x-4=-2(3x+5) clear the fraction. 3x-4=-6x-10 add+6x+4 to ...

Algebra - How do I factor out the greatest common monomial factor? 1) 9m^7 - 3m^...

Math - Factorising - Find the quotient and the remainder in the following. a). x...

Math - Differentiate g(x)=(x^3+1)(3x^2-1) so I use g'(x) X h(x) + g(x) X h'(x) ...